Mapping relief units and geosites of Seridó UNESCO Global Geopark, Northeastern Brazil - Marco Tulio Mendonca Diniz; George Pereira de Oliveira; Diogo Bernardino Santos de Medeiros; Jucielho Pedro da Silva; Marcos Antonio Leite do Nascimento; Matheus Dantas das Chagas; Antonio Carlos Barros Correa; Vanda Claudino-Sales (Revista Brasileira de Geomorfologia)
The Seridó UNESCO Global Geopark (SUGG) was approved in 2022. In all, the Geopark has 21 geosites, the main interest of which is geomorphological. Despite the importance of the geomorphological heritage in the SUGG territory, the area had not yet been mapped on a scale suitable for geoconservation actions by the SUGG technical staff and its scientific committee. The present work aims to identify landforms up to the fourth taxon, corresponding to types of relief forms, according to Ross's (1992) methodological proposal for the geomorphological mapping of Brazil. Landform hierarchy was established following the morphological taxon typology proposed by the RadamBrasil Project and described by Ross (1992). The first three taxons correspond to those of Diniz et al. (2017) for the Rio Grande do Norte geomorphological map. However, for this study, the fourth taxon was added. This scale and taxonomic level were considered suitable for geoconservation actions. Maps are also presented at higher taxonomic levels, with less detail, which are more suitable for geoeducation activities with schoolchildren in the SUGG territory.